EP381 The role of diagnostic laparoscopic in locally advanced cervical cancer staging in the bevacizumab era. (1st November 2019) - Bizzarri, N; Pedone Anchora, L; Teodorico, E; Lombisani, A; Di Fiore, G; Gallotta, V; Gueli Alletti, S; Ghirardi, V; Conte, C; Fagotti, A; Scambia, G; Ferrandina, G
Abstract : Introduction/Background: The benefit of surgical staging with laparoscopy remains controversial and the prognostic significance of peritoneal involvement in locally advanced cervical cancer (LACC) patients has still to be demonstrated. Peritoneal involvement upstages cervical cancer to FIGO stage IVB, which can benefit from addition of bevacizumab to standard chemotherapy, after FDA approval. The aim of this study is to determine the rate of peritoneal involvement in a large series of LACC. Methodology: Retrospective cohort study approved by the Institutional Review Board. Patients with newly diagnosed LACC (FIGO stage IB2-IVA) and metastatic cervical cancer (FIGO stage IVB), were included. All women underwent diagnostic laparoscopy with peritoneal biopsy at the time of examination under anesthetic (EUA) and cystoscopy between March 2015 and December 2018, during staging of cervical cancer. Clinical and surgical characteristics were extracted from electronic records. Results: 201 patients underwent EUA in the study period.Of these 9 (4.4%) did not undergo diagnostic laparoscopy. 192 women underwent diagnostic laparoscopy: 171 (89.1%) LACC, 21 (10.9%) IVB (distant/parenchymal metastases). No intra- or post-operative complication was recorded. Peritoneal involvement was present in 30/192 (15.6%) women and it was histologically confirmed in all cases. 18/30 (60%) cases had only pelvic peritoneal involvement, 9/30 (30%) had both pelvic and upper-abdominal involvement, while 3/30 (10%) had only upper-abdominal involvement. PET/CT-scan and MRI-scan detected peritoneal carcinomatosis in 3/30 (10.0%) and 2/30 (6.7%) patients, respectively. In 21/30 (70%) cases, laparoscopy upstaged the tumour to FIGO stage IVB and changed the treatment plan. 9/30 (30%) were staged as IVB for distant/parenchymal metastases (independently from laparoscopic findings). 15/30 (50%) cases underwent chemotherapy+bevacizumab. Conclusion: Diagnostic laparoscopy as part of cervical cancer staging is an important tool to detect unexpected peritoneal disease and change therapeutic management of LACC patients. Disclosure: Nothing to disclose.